Effect of Thickness on Qualities of Dried Sweet Bamboo Shoots (Dendrocalamus asper Backer) Products - Charoenphun, Narin; Pakeechai, Kanokporn (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this research was to investigate the effect of thickness on the quality of dried sweet bamboo shoots (SBS). The SBS were prepared with various thicknesses. The quality of dried SBS was investigated, including weight loss, lightness, hardness, and sodium chloride content. The results indicated that the weight loss and the amount of sodium chloride tended to decrease when the thickness of SBS increased. Conversely, the brightness and hardness varied directly as the thickness of SBS. The effect of thickness on drying time and rehydration time using different methods of SBS were studied. The results showed that the SBS with a thickness of 2 mm had the shortest drying time and rehydration time. The dried SBS was soaked in water at room temperature for 30 min before boiling in hot water. This method had the shortest rehydration time when compared with other methods. The sensory evaluation of dried SBS after rehydration by untrained panelists were investigated. It was found that SBS with a thickness of 2 mm had the highest scores on sensory acceptability in appearance, color, texture, flavor, and overall liking score. The analysis of the chemical composition of dried SBS was high carbohydrate (48.18%), protein (22.52%), and low-fat content (4.18%). The shelf life of dried SBS product was at least 6 months. Accordingly, the knowledge gained from this study can be applied to the production of dried SBS, which can extend the shelf life of SBS and added value of agricultural products.